From Mission Schools to Private Universities: The Historical Trajectory of Christian Education in Nigeria - Karibo, Innocent (NIU Journal of Educational Research, 2025)
The history of Christian education in Nigeria reveals a complex trajectory that spans from the pioneering mission schools of the nineteenth century to the proliferation of faith-based private universities in the twenty-first century. Early mission schools established by the Church Missionary Society, the Wesleyan Methodist Mission, and the Roman Catholic Mission functioned as centers of literacy, evangelization, and social transformation, producing the first generation of Nigerian elites who later shaped politics, church leadership, and nationalist movements. However, the post-independence government takeover of mission schools in the 1970s, justified on grounds of standardization and secularization, eroded much of the moral and religious ethos embedded in Christian education, resulting in widespread concerns over declining standards and weakened character formation. The liberalization of the higher education sector in 1999 marked a new phase, leading to the establishment of private Christian universities such as Covenant, Babcock, Bowen, and Madonna Universities. These institutions sought to revive the integration of faith and learning while offering alternatives to overstretched public universities. Yet, tensions persist: questions of elitism, commercialization, and the extent to which private universities continue the legacy of holistic Christian education remain unresolved. This study critically examines the historical shifts, continuities, and contradictions within this educational trajectory, with particular attention to its philosophical, theological, and socio-political underpinnings. Keywords: Christian Education, Mission Schools, Private Universities, Secularization, Evangelization, Neoliberalism, Nation-building.